The Absence of Constitutional Complaints in the Authority of the Constitutional Court Regarding the Protection of Public Benefit Rights in Indonesia - Dinda Rambe (Islamic Research Publiser, 2023)
The majority of constitutional complaints that enter the Constitutional Court are constitutional, but because they are not meant to be the authority of legal examination of the 1945 UUD, the Court often rejects them and allows them to take place